Strategi Pengembangan Kawasan Ekowisata Untuk Meningkatkan Jumlah Kunjungan Wisatawan - Jovita Vicka Bayu Wardhani; Regina Mayo (University of Merdeka Malang, 2017)
A tourist area, especially nature tourism, can actually be innovated/added value without destroying the nature. The one way is to pack it into an ecotourism area. Sempu Island which is located in Kabupaten Malang is one of the interesting example on how the ecotourism concept could be combined to the local economic development and conservation issues. The purpose of this research are : 1) identify local economic strengths that exist in the Ecotourism Area of Sendang Biru Beach, 2) strategy compile that can encourage the development of ecotourism potential in order to increase the number of tourists visiting on the Sendang Biru Beach. This research uses qualitative approach. The type of data are primary and secondary data. Method of data analysis uses a SWOT matrix analysis. The results of field research indicates that Sendang Biru Beach has the potential to become an ecotourism area. The strategy to develop the area of ​​Sendang Biru Beach into an ecotourism area are ; 1) Equating perceptions of ecotourism among local communities, stakeholders and tourists, 2) Improving and rearranging infrastructure in Sendang Biru Beach. https://doi.org/10.26905/jmdk.v5i2.1635